Clinical Manifestation of Depression in Adolescent: A Literature Review - Putri, Ajeng Ayu; Hermansyah, Anang; Faranajhia, Hagia; Gifari, Lalu Maulana Azmi; Zakiyyah, Luthfi; Fauzan, Muhammad; Amatullah, Tazkiyah Arafah; Adni, Azizatul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Adolescence is a critical phase in physical, cognitive and psychosocial development that can affect mental health. Depression is a major concern in this group, characterized by mood swings, loss of interest, and decreased energy. This article aims to review the epidemiology, etiology, clinical manifestations, and treatment options of depression in adolescents. The method used was a literature review of various related studies. Results show that genetic factors, cognitive vulnerability, and environmental influences, such as family relationships and social media use, contribute to the emergence of depressive symptoms in adolescents. In addition, the increasing prevalence of cyberbullying correlates with high levels of emotional distress and suicidal ideation among adolescents. Treatment approaches include pharmacological interventions, especially SSRIs such as fluoxetine and escitalopram, as well as non-pharmacological therapies such as Cognitive Behavioral Therapy (CBT) and family-based psychosocial support. In conclusion, recognizing and effectively treating depression in adolescents is critical to improving long-term outcomes and building their mental resilience.